1997
DOI: 10.1093/cercor/7.1.48
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corpus callosum size and forebrain volume

Abstract: Using high-resolution in vivo magnetic resonance morphometry we measured forebrain volume (FBV), midsagittal size of the corpus callosum (CC) and four CC subareas in 120 young and healthy adults (49 women, 71 men). We found moderate linear and quadratic correlations, indicating that the CC and all CC subareas increase with FBV both in men and women (multiple r2 ranging from 0.10 to 0.28). Allometric equations revealed that these increases were less than proportional to FBV (r2 ranging from 0.02 to 0.30). Absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
193
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(227 citation statements)
references
References 45 publications
(93 reference statements)
32
193
2
Order By: Relevance
“…The CC is smaller in smaller brains (Jancke et al, 1997). More specifically, a smaller auditory cortex presumably gives rise to a smaller number of callosal fibers crossing to the contralateral side.…”
Section: Introductionmentioning
confidence: 99%
“…The CC is smaller in smaller brains (Jancke et al, 1997). More specifically, a smaller auditory cortex presumably gives rise to a smaller number of callosal fibers crossing to the contralateral side.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicats that foot CMFs are generally located in the posterior part of the CC, occupying approximately one-third of its portion. In a previous study, Jancke et al showed that the distance ratio of the isthmus was generally located in 20-33.3% of the posterior portion of the CC, based on dividing the length of the structure into three equal portions, namely, the anterior third, middle third, and posterior third, including the isthmus and splenium 9) . Based on this result, we attempted to identify a more detailed relative anatomical location within the isthmus, which is located in the posterior third portion of the CC.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have investigated the anatomical and functional characteristic of the CC in humans 2,7,9,10,13,16,18,25) . These studies investigated the thickness, volume, and area information of the CC to provide accurate anatomical information 9,10,25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations